Raising the Stakes for Online Learning: Monetary Incentives Increase Performance in a Computer-Based Learning Task Under Certain Conditions - Schwab, Jessica F.; Somerville, Leah H. (Frontiers in Psychology, 2022)
To what extent can external incentives influence students’ effort and learning in online course contexts? While cognitive science research has found that monetary incentives can increase goal-directed cognitive effort in certain laboratory tasks, attempts to use monetary incentives to increase students’ academic performance in naturalistic settings has shown mixed results. In two experiments, we tested the influence of a monetary incentive (compared to no external incentive) on immediate and delayed tests of computer-based educational performance (i.e., learning from educational videos). In Experiment 1, participants were assigned to (1) receive monetary incentives for correct quiz responses, or (2) to receive no additional incentive for correct responses other than finding out their score, and we found no significant difference in total score across groups (on either immediate or delayed tests of learning). In Experiment 2, we used a within-subjects design to test whether participants performed better when they were provided monetary incentives for correct responses on quiz questions (compared to no external incentive). Here, participants performed significantly better on incentivized quiz questions (on both immediate and delayed tests of learning). Thus, monetary incentives may increase performance in online learning tasks when participants can anchor the “stakes” of an incentive compared to no external incentive. These findings highlight potential benefits of external incentives for promoting effort and learning in online contexts, although further research is needed to determine the most useful educationally-relevant extrinsic incentives, as well as potential negative effects of incentives on long-term intrinsic motivation.